(untitled) (Modern Problems of Metallurgy, 2019)
Thermal spraying is actively used in microelectronics and optics, in particular, spraying of anti-reflective and reflective coatings is done by the method. The purpose of this work is to study the dependence of the thickness of metal films on the time of deposition in a vacuum. In order to find out whether the metal atoms collide with the evaporation of the residual gas molecules in the chamber as it moves towards the glass substrate, and also that their trajectory is straight, we calculate the average path length of the molecule. If the distance from the evaporator to the substrate in the vacuum chamber is sufficiently small compared to the average mean free path of the molecule, then most of the metal atoms will reach the substrate without colliding with the residual gas molecules. A number of measurements were made of the resistance of metal films obtained by sputtering in vacuum, and the physical processes of deposition of zinc from the vapor – gas phase were studied in vacuum. Based on the experimental data obtained, the dependence of the thickness of metal films on the time of deposition was revealed.